Higher order complex Szász-Kantorovich operators - Kara, Mustafa; Mahmudov, Nazim Idrisoglu (MTJPAM Turkey, 2024)
This paper introduces a novel type of generalized complex Szász-Kantorovich operators. Subsequently, we establish quantitative estimates within Voronovskajaís theorem, determining precise orders for approximating analytic functions. Notably, our approach eliminates the need for imposing exponential growth conditions on compact disks when considering these operators. © 2024, MTJPAM Turkey. All rights reserved.
Keywords: exact estimates; Szasz-Kantorovich operator; Voronovskaja type theorem